Acordo de acionistas e qualidade das informações contábeis : evidências empíricas no mercado brasileiro - Lyrio, Felipe Maia (2013)
The goal of the thesis is to assess the influence of shareholders’ agreement in the quality of bookkeeping information released by the companies listed on BM&FBOVESPA, from 2001 to 2011. In order to infer about the quality of the bookkeeping information, informativeness metrics and value relevance were used. The command agreement (used to guarantee the control) of the defense agreements (used to guarantee the access to certain rights by reaching a minimal percentage of voting capital). The sample had as cutting criterion the minimum of 0.001 liquidity in BM&FBOVESPA. The multiple linear regression with unbalanced panel data was used, having as control variables: concentration of votes, size, debt incurring, market-to-book and losses. Based on achievement and monitoring effects, using the methodology proposed, the study shows that companies with any kind of agreements among shareholders have more quality of the released bookkeeping profits.